Touch n Go e-Wallet: The New Payment Style Existed when COVID-19 Hits - Muhammad Daniel Bin Ahmad Izaidin; Vijay Anant Athavale; Muhammad Danial Bin Abdul Razak; Nafisa Hani Binti Mohamed Zain; Najla Awatif Binti Aqimu’ Ajiby; Sakshi Singh; Yash Rajendra Katkar (AIBPM Publisher, 2022)
Touch ‘n Go e-wallet is a smartphone application that has recently gained users since the pandemic of COVID-19 hits Malaysia. Touch ‘n Go is an e-wallet, an electronic card that can make online payments using a smartphone. It is a secure way to pay using a smartphone because it is convenient to use and reduces physical touch, which can spread diseases and germs to other people. The pandemic and the imposition of Movement Control Orders (MCO) and Home Quarantine have encouraged e-wallet usage, as people will choose cashless payments during that period. This study examines how e-wallets help consumers throughout the COVID-19 pandemic in Malaysia. A total of 150 consumers completed an online survey via Google Forms, and the data were analyzed using SPSS. We found that perceived ease of use and trust impacted consumer satisfaction. This research provides new insights on e-wallet perceptions of Touch n Go and how this perception may promote consumer satisfaction.Keywords: COVID-19, E-wallet, MCO, Pandemic, Physical touch, Smartphone, Touch n Go